Successful non-surgical treatment of pseudomonas choroidal abscess in cystic fibrosis with previous double lung transplantation. Issue 1 (13th January 2022) - Pujari, Rathin; Bhatia, Bhairavi; Damato, Erika Marie; Alexander, Philip
Abstract : Pseudomonas aerugino sa choroidal abscess is a rare condition which tends to affect patients with cystic fibrosis (CF) who have undergone double lung transplantation. Various surgical treatment strategies have been described but almost universally have had a dismal prognosis. We present a case of pseudomonas choroidal abscess in a CF patient with previous double lung transplantation who was managed with medical treatment, with intravitreal and systemic antibiotics, without surgical intervention, which led to successful resolution of the choroidal abscess, preservation of the eye and retention of vision.